The influence of tax authority services, tax socialization, and tax policy on taxpayer compliance, with risk preferences as a moderating variable in the voluntary disclosure program in Ternate City - Kotta, Oktofianus Franszeblum; Morasa, Jenny; Warongan, Jessy D. L. (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to determine the influence of tax authorities services, tax socialization, and tax policy on taxpayer compliance with risk preferences as a moderating variable during the Voluntary Disclosure Program in Ternate City. The sample is the taxpayers and the data is obtained by questionnaire based on a Likert scale. This study applies structural equation model - partial least square to explain the correlation between indicators in construct variables (convergent validity test), test the consistency of the measuring instrument used (reliability test), and measure the extent to which a construct is different from other constructs (validity test discriminant). The coefficient of determination is carried out to explain the proportion of the dependent variable explained by the independent variable, the path coefficient test to explain the direction of the relationship between the independent variable and the dependent variable, and the effect size test to see how the independent variables to predict the dependent variable. The results show that partially tax authorities' services do not have a significant influence on taxpayer compliance, while tax socialization, tax policy, and risk preferences have a significant influence on taxpayer compliance. Risk preferences moderate the influence of tax authorities' services and tax socialization on taxpayer compliance, but do not moderate the influence of tax policy on taxpayer compliance in the Voluntary Disclosure Program in the Ternate City.